Retailer’s Service Quality & CSR as Antecedents of Retailer Personality & Customer Reactions: A Review - Rashid, Abdul; Rokade, Varsha (Ushus Journal of Business Management, 2022)
This research paper aims to assess the influence of Retail Service Quality and CSR as antecedents of Retailer Personality and Customer Reactions. Also, reviews were done for studies which implemented Analytic Hierarchy Process (AHP). The relationships and links were identified from a rigorous literature review. A conceptual model has been developed and proposed, with Retail Service Quality and CSR Policy of retailer as antecedents and Customer Reactions as consequences of Retailer Personality. Hypotheses were formulated, recommendations and Scope for future research were discussed.